PENGARUH PEJANTAN DAN PAKAN TERHADAP GENOTIP PERTUMBUHAN ITIK TURI - Dewanti, Ratih (Caraka Tani: Journal of Sustainable Agriculture, 2010)
The experiment was carried out to observe the effect of sires and diets on the growth of genotype traits of Turi duck. There were five sires and 25 dams which produced 151 offspring used in the experiment. Three diets with equal nutrient balance but different concentration P1: {CP:EM= 1:145, EM 2482 kcal/kg:protein 17%}; P2 {CP:EM= 1:146 EM 2628 kcal/kg: protein 18%}; and P3 {CP:EM= 1:144 (EM 2774 kcal/kg: protein 19%} were then applied. Heritability estimation on body weight sire wise was h2: 0.059 (1st week); h2: 0.096 (2nd week), while the estimated heritability for body weigght gain was h2: 0.063 (1st week), h2: 0.239 (2nd week), h2: 0.062 (3rd week), h2: 0.156 (5th week), h2: 0.278 (6th week) and h2: 0.046 (8th week) respectively.